Predicting yields using biophysical crop simulations, machine learning and remote sensing in India - CGIAR Platform for Big Data in Agriculture (2020)
We tested the innovation and piloted it using ground truth yield data collected by means of crop cutting experiments in Odisha. Before starting to finalize the tool for adoption by insurance providers, the tool will be fine-tuned in the course of 2021.